Criminal Liability for Online Gambling Practices Based on Chapter 27 Paragraph (2) and Chapter 45 Paragraph (2) of Law Number 1 of 2024 - Kresna Satria Wibowo; Brahma Astagiri (International Journal of Science and Environment (IJSE), 2026)
The practice of online gambling in Indonesia is increasingly widespread and has given rise to various new problems which have resulted in many changes to the increasingly advanced system. The practice of online gambling is currently still a major problem with a variety of more complex cases in the digital system. This research aims to analyze how Law Number 2024 (UU ITE) is able to solve problems related to online gambling practices. The method used in this research is normative law with the aim of examining legal norms relating to overcoming online gambling practices in Indonesia through Law Number 1 of 2024 concerning Information and Electronic Transactions (UU ITE). The research results show that Article 27 paragraph (2) of the ITE Law states that a person who intentionally and without the right distributes, transmits and/or makes accessible Electronic Information and/or Electronic Documents containing gambling content can be punished in accordance with the applicable provisions in accordance with Article 45 paragraph (3) of the ITE Law.